2014
DOI: 10.1016/j.dld.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

An a priori prediction model of response to peginterferon plus ribavirin dual therapy in naïve patients with genotype 1 chronic hepatitis C

Abstract: Peg-interferon and ribavirin treatment Predictors of sustained virological response, Rapid virological response a b s t r a c t Background: Aim was to select naïve patients with genotype 1 chronic hepatitis C having a high probability of response to Peg-interferon + ribavirin therapy. Methods: In 1073 patients (derivation cohort), predictors of rapid and sustained virological response were identified by logistic analysis; regression coefficients were used to generate prediction models for sustained virological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…These patients with high baseline HCV-RNA and advanced fibrosis are in urgent need for new therapeutic approaches and should be prioritized when sofosbuvir or other antivirals become available. A similar approach was recently proposed to identify a sub-group of patients infected with HCV genotype 1 who might benefit from peginterferon plus RBV therapy [32] . Owing to its retrospective nature, our study has several limitations.…”
Section: Virologic Responsementioning
confidence: 99%
“…These patients with high baseline HCV-RNA and advanced fibrosis are in urgent need for new therapeutic approaches and should be prioritized when sofosbuvir or other antivirals become available. A similar approach was recently proposed to identify a sub-group of patients infected with HCV genotype 1 who might benefit from peginterferon plus RBV therapy [32] . Owing to its retrospective nature, our study has several limitations.…”
Section: Virologic Responsementioning
confidence: 99%
“…In this regard, several scientific societies and studies have declared that, until global access to DAAs is guaranteed, treatment-naïve patients exhibiting favorable clinical, genetic, and virologic profiles could still benefit with the PEG-IFN/RBV regimen; thus restricting the use of newer and expensive treatment schemes for “difficult to treat” patients 22,29,41,70,8487…”
Section: Resultsmentioning
confidence: 99%
“…20,21 27 This study determined that SVR was strongly associated with RVR (OR=21) and cEVR (OR=11) in patients with HCV genotype-1 infection, which confirms the same observation determined previously among non-hemophilic HCV-infected individuals and indicates the importance of a rapid drop in HCV RNA level on HCV eradication. 28 Andriulli et al 29 found that achieving RVR was the main on-treatment predictor for achieving SVR. The current study demonstrated that attaining RVR played more of a key role in attaining SVR than either of the polymorphisms of the IFNL4 gene.…”
Section: Discussionmentioning
confidence: 99%